Mechanisms of Immunothrombosis by SARS-CoV-2 - María Teresa Hernández-Huerta; Alma Dolores Pérez-Santiago; Laura Pérez-Campos Mayoral; Luis Manuel Sánchez Navarro; Francisco Javier Rodal Canales; Abraham Majluf-Cruz; Carlos Alberto Matias-Cervantes; Eduardo Pérez-Campos Mayoral; Carlos Romero Díaz; Gabriel Mayoral-Andrade; Margarito Martínez Cruz; Judith Luna Ángel; et al. (Biomolecules, 2021)
SARS-CoV-2 contains certain molecules that are related to the presence of immunothrombosis. Here, we review the pathogen and damage-associated molecular patterns. We also study the imbalance of different molecules participating in immunothrombosis, such as tissue factor, factors of the contact system, histones, and the role of cells, such as endothelial cells, platelets, and neutrophil extracellular traps. Regarding the pathogenetic mechanism, we discuss clinical trials, case-control studies, comparative and translational studies, and observational studies of regulatory or inhibitory molecules, more specifically, extracellular DNA and RNA, histones, sensors for RNA and DNA, as well as heparin and heparinoids. Overall, it appears that a network of cells and molecules identified in this axis is simultaneously but differentially affecting patients at different stages of COVID-19, and this is characterized by endothelial damage, microthrombosis, and inflammation.